Pengaruh Selebgram Endorsement dan E-Wom terhadap Keputusan Pembelian Konsumen Bittersweet by Najla melalui Niat Beli - Meliana Angelia; William Widjaja (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the impact of celebrity Instagram endorsements and e-WOM on the purchasing decisions of bittersweet consumers through purchase intention. Methodology/approach: The research method used was ex post facto with a quantitative approach. Non-probability sampling was the sampling technique employed. Questionnaires were the primary means of data collection. Data analysis was conducted using SmartPLS tools. Results: Celebrity Instagram endorsements have a positive and significant impact on purchase intention and purchase decisions. Purchase intention also had a positive and significant impact on purchasing decisions. However, e-WOM does not have a significant impact on purchase intentions or purchase decisions. The results of the hypothesis testing for indirect effects indicate that celebrity Instagram endorsements have a positive and significant impact on purchase decisions mediate purchase intention, but purchase intention does not successfully mediate the influence of e-WOM on purchasing decisions. Limitations: This research does not cover the entire consumer population of Bittersweet By Najla, which is only represented by 103 respondents. The variables used by researchers do not fully fulfill the influence of purchasing intentions and decisions. The variables used by researchers can also be expanded by using other variables. Contribution: Based on the results of the research that has been carried out, the researcher wants to provide input to Bittersweet using Najla as a research object: Researchers suggest that Bittersweet by Najla can endorse honest celebrities, such as Titan Tyra. Researchers have also suggested that Bittersweet by Najla makes social networks as attractive as possible. Research suggests that Bittersweet by Najla can develop more food products so that if consumers do not eat the products, they will feel less.